An OSEK/VDX-based Multi-JVM for Automotive Appliances - Wawersich, Christian; Stilkerich, Michael; Schröder-Preikschat, Wolfgang (Embedded System Design: Topics, Techniques and Trends, 2007)
The automotive industry has recent ambitions to integrate multiple applications from different micro controllers on a single, more powerful micro controller. The outcome of this integration process is the loss of the physical isolation and a more complex monolithic software. Memory protection mechanisms need to be provided that allow for a safe co-existence of heterogeneous software from different vendors on the same hardware, in order to prevent the spreading of an error to the other applications on the controller and leaving an unclear responsibility situation. With our prototype system KESO, we present a Java-based solution for robust and safe embedded real-time systems that does not require any hardware protection mechanisms. Based on an OSEK/VDX operating system, we offer a familiar system creation process to developers of embedded software and also provide the key benefits of Java to the embedded world. To the best of our knowledge, we present the first Multi-JVM forOSEK/VDX operating systems. We report on our experiences in integrating Java and an embedded operating system with focus on the footprint and the real-time capabilities of the system. © International Federation for Information Processing 2007.
UnivIS-Import:2015-04-16:Pub.2007.tech.IMMD.IMMD4.anosek
Keywords: KESO